Cutaneous and acral melanoma cross-OMICs reveals prognostic cancer drivers associated with pathobiology and ultraviolet exposure - Anna Luiza Silva Almeida Vicente; Alexei Novoloaca; Vincent Cahais; Zainab Awada; Cyrille Cuenin; Natália Spitz; André Lopes Carvalho; Adriane Feijó Evangelista; Camila Souza Crovador; Rui Manuel Reis; Zdenko Herceg; Vinicius de Lima Vazquez; et al. (Nature Communications, 2022)
While cutaneous melanoma is linked to UV radiation, acral melanoma is not. Epigenetic mechanisms function as sensors to exposures and determinants of cell identity. Here, the authors use DNA methylation data to identify dysregulated pathways associated with UV radiation and pathobiology in cutaneous and acral melanomas.